Comparison of absolute fluid restriction versus relative volume redistribution strategy in low central venous pressure anesthesia in liver resection surgery: a randomized controlled trial - Zatloukal, Jan; Pradl, Richard; Kletecka, Jakub; Skalicky, Tomas; Liska, Vaclav; Benes, Jan (Minerva anestesiologica, 2017)
BACKGROUNDː Lowering central venous pressure (CVP) can decrease blood loss during liver resection and it is associated with improved outcomes. Multiple CVP reducing maneuvers have been described, but direct comparison of their effectiveness and safety has never been performed. METHODSː Patients undergoing resections of two or more liver segments were equally randomized to absolute fluid restriction (AR, N.=17) or relative volume redistribution group (RR, N.=17). The ease of reaching low CVP, blood loss, morbidity and mortality were assessed. Besides, the effect of Pringle maneuver and utility of stroke volume variation (SVV) were analyzed. RESULTSː Both methods of CVP reduction were equally effective (0.7±0.9 vs. 0.9±1.0 protocolized steps in the AR and RR group; P=0.356) and safe (no difference in observed blood loss, intraoperative hemodynamic parameters, lactate levels, morbidity and mortality). Patients in the AR group received smaller amount of fluids in the pre-resection period (120 (100-150) vs. 600 (500-700) mL; P<0.001), and had slightly longer hospital stay (10 [8-14] vs. 8 [7-11]; P=0.045). Low CVP was predicted by SVV>10% with 81.4% sensitivity and 77.1% specificity. Reduced blood loss and transfusion rate was observed when Pringle maneuver was used. CONCLUSIONSː In our study, absolute fluid restriction and relative volume redistribution seemed to be equally effective and safe methods of lowering CVP in patients undergoing liver resection. According to our data high SVV might be considered as a low CVP replacement. Pringle maneuver reduced blood loss and transfusion requirement.
Keywords: Male; anestezie; tekutinová terapie; Intraoperative Care; centrální žilní tlak; Central Venous Pressure; krvácení při operaci; Prospective Studies; mužské pohlaví; lidé; Hepatectomy; ženské pohlaví; Humans; Anesthesia; Blood Loss, Surgical; peroperační péče; Female; Fluid Therapy; hepatektomie; lidé středního věku; Middle Aged; prospektivní studie